Severity of Coronary Artery Disease in Patients with or without Diabetic Retinopathy - Muhammad Saleem, Muhammad Mohsin, Hamdan Waqas (Journal of Rawalpindi Medical College, 2017)
Background: To determine the frequency of diabetic retinopathy in type 2 diabetic patients undergoing angiographic evaluation and compare the severity (Mean vessel score and mean Gensini score) of coronary artery disease in patients with or without diabetic retinopathy. Methods: In this cross sectional study, 300 diabetic patients, with suspected coronary artery disease undergoing coronary angiography, were included. All the patients were assessed for the presence or absence of diabetic retinopathy and severity of coronary artery disease. Results: One hundred and three out of 300 patients (34.3%) had diabetic retinopathy. In patients with diabetic retinopathy, the mean vessel score was 2.62 + 0.60 as compared to 1.90 + 1.03 in non retinopathy group (p=0.000). Gensini score was also found to be significantly higher in diabetic retinopathy group (103 + 37.17 versus 38.5508 + 22.205) (p=0.000). Conclusions: Severity scores (Vessel and Gensini scores) of coronary artery disease were significantly higher in patient with diabetic retinopathy as compared to those without diabetic retinopathy.